Biogas crops grown in energy crop rotations: Linking chemical composition and methane production characteristics. (April 2016) - Herrmann, Christiane; Idler, Christine; Heiermann, Monika
Highlights: Methane formation characteristics from 405 silages of 43 crop species are presented. Silages from a wide range of crop species are well suited for biogas production. Besides lignin, products of silage fermentation significantly affect methane yield. The content of nitrogen-free extracts mainly determines methane contents. The fibre fraction has the largest impact on the rate of methane production. Abstract: Methane production characteristics and chemical composition of 405 silages from 43 different crop species were examined using uniform laboratory methods, with the aim to characterise a wide range of crop feedstocks from energy crop rotations and to identify main parameters that influence biomass quality for biogas production. Methane formation was analysed from chopped and over 90 days ensiled crop biomass in batch anaerobic digestion tests without further pre-treatment. Lignin content of crop biomass was found to be the most significant explanatory variable for specific methane yields while the methane content and methane production rates were mainly affected by the content of nitrogen-free extracts and neutral detergent fibre, respectively. The accumulation of butyric acid and alcohols during the ensiling process had significant impact on specific methane yields and methane contents of crop silages. It is proposed that products of silage fermentation should be considered when evaluating crop silages for biogas production.